Particle and organic vapor emissions from children's 3-D pen and 3-D printer toys. (6th December 2019) - Yi, Jinghai; Duling, Matthew G.; Bowers, Lauren N.; Knepp, Alycia K.; LeBouf, Ryan F.; Nurkiewicz, Timothy R.; Ranpara, Anand; Luxton, Todd; Martin, Stephen B.; Burns, Dru A.; Peloquin, Derek M.; Baumann, Eric J.; et al.
Abstract: Objective: Fused filament fabrication "3-dimensional (3-D)" printing has expanded beyond the workplace to 3-D printers and pens for use by children as toys to create objects. Materials and methods: Emissions from two brands of toy 3-D pens and one brand of toy 3-D printer were characterized in a 0.6 m 3 chamber (particle number, size, elemental composition; concentrations of individual and total volatile organic compounds (TVOC)). The effects of print parameters on these emission metrics were evaluated using mixed-effects models. Emissions data were used to model particle lung deposition and TVOC exposure potential. Results: Geometric mean particle yields (10 6 –10 10 particles/g printed) and sizes (30–300 nm) and TVOC yields (<detectable to 590 µg TVOC/g printed) for the toys were similar to those from 3-D printers used in workplaces. Metal emissions included manganese (1.6–92.3 ng/g printed) and lead (0.13–1.2 ng/g printed). Among toys, extruder nozzle conditions (diameter, temperature) and filament (type, color, and extrusion speed) significantly influenced particle and TVOC emissions. Dose modeling indicated that emitted particles would deposit in the lung alveoli of children. Exposure modeling indicated that TVOC concentration from use of a single toy would be 1–31 µg/m 3 in a classroom and 3–154 µg/m 3 in a residential living room. Discussion: Potential exists for inhalation of organic vapors and metal-containing particles during use of these toys. Conclusions: If deemed appropriate, e.g. where multiple toys are used in a poorly ventilated area or a toy is positioned near a child's breathing zone, control technologies should be implemented to reduce emissions and exposure risk.